1996
DOI: 10.1117/1.601113
|View full text |Cite
|
Sign up to set email alerts
|

Long‐working‐distance microscope used for diesel injection spray imaging

Abstract: An optical system for analysis of diesel spray penetration and atomization has been developed. The basic system is based on a microscope with a long working distance (230 mm) and a modest resolution. The magnification is variable between 1:1 and 50:1 on the camera plane. This enables the study of individual droplets with a diameter of 5 m. A number of different techniques have been used together with the basic system to study different parts of the spray. They include the darkground technique, double exposure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…This indicates that @ 2 n=@x 2 increases from the ambient gas to the residual fluid, which in turn shows that the density also increases along that direction. We conclude from this The translucent appearance of the residual fuel (frames 1-4) allowed the fresh fuel to be independently tracked as it penetrates through the residual liquid fuel (frames [5][6][7][8][9][10][11][12]. See [29] or supplemental material for the full video [29].…”
Section: Emergence Of Fuel From the Orificementioning
confidence: 95%
See 1 more Smart Citation
“…This indicates that @ 2 n=@x 2 increases from the ambient gas to the residual fluid, which in turn shows that the density also increases along that direction. We conclude from this The translucent appearance of the residual fuel (frames 1-4) allowed the fresh fuel to be independently tracked as it penetrates through the residual liquid fuel (frames [5][6][7][8][9][10][11][12]. See [29] or supplemental material for the full video [29].…”
Section: Emergence Of Fuel From the Orificementioning
confidence: 95%
“…Microscopic imaging experiments of diesel sprays have been reported in the literature (e.g. [5,[10][11][12][13]), although at atmospheric conditions and with varying degrees in the quality of the images produced. Satisfactory lighting can be particularly difficult to obtain at microscopic level.…”
Section: Introductionmentioning
confidence: 98%
“…Gasoline-like fuels are referred to as low reactivity fuels due to their low ignitability. Gasoline-like fuels that perform with high ignition delays, leading to longer mixing times due to their low reactivity, have recently been tested in advanced combustion strategies to improve the mixing of fuel and air [6][7][8][9][10][11]. It was reported that gasoline-like fuels are advantageous in achieving mid-to-high load conditions with significantly low fuel consumption and emissions, but with high emissions of HC and CO and combustion instability under low load conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1 The overall shape of a spray, and its penetration length into the receiving media, can be measured by means of photography, either direct or backlit by flash lamp or laser. 2 The extent of the vapor cloud surrounding the spray can be seen by means of schlieren imaging 3 or laser-induced fluorescence ͑LIF͒ of the fuel vapor. 4 However, measuring the internal properties of a spray, such as its breakup from bulk liquid into smaller droplets, their size and number density, is difficult.…”
Section: Introductionmentioning
confidence: 99%